2021
DOI: 10.5395/rde.2021.46.e54
|View full text |Cite
|
Sign up to set email alerts
|

Change of phase transformation and bond strength of Y-TZP with various hydrofluoric acid etching

Abstract: Objectives The purpose of this study was to quantify phase transformation after hydrofluoric acid (HF) etching at various concentrations on the surface of yttria-stabilized tetragonal zirconia polycrystal (Y-TZP), and to evaluate changes in bonding strength before and after thermal cycling. Materials and Methods A group whose Y-TZP surface was treated with tribochemical silica abrasion (TS) was used as the control. Y-TZP specimens from each experimental group were etche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Finally, the tetragonal-to-monoclinic ( t – m ) phase transformation, which is a critical consideration for the surface treatment of Y-TZP ceramics, was not evaluated in this study. Previous studies demonstrated that gentle air abrasion protocols, as used in this study, generally trigger t – m phase transformation 42 44 , whereas HF etching with conditions close to the current study was found to induce phase transformation to the lesser degree than air abrasion 45 . Nevertheless, such a small amount of monoclinic phase presented on the zirconia surfaces prior to the bonding procedure was found to not influence the resin bond strength 45 47 .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Finally, the tetragonal-to-monoclinic ( t – m ) phase transformation, which is a critical consideration for the surface treatment of Y-TZP ceramics, was not evaluated in this study. Previous studies demonstrated that gentle air abrasion protocols, as used in this study, generally trigger t – m phase transformation 42 44 , whereas HF etching with conditions close to the current study was found to induce phase transformation to the lesser degree than air abrasion 45 . Nevertheless, such a small amount of monoclinic phase presented on the zirconia surfaces prior to the bonding procedure was found to not influence the resin bond strength 45 47 .…”
Section: Discussionsupporting
confidence: 65%
“…After aging, the increase in monoclinic contents 48 and the decrease in bond strengths of resin-zirconia 45 , 49 , 50 were widely reported. However, the study revealing the negative correlation between monoclinic contents and bond strengths after aging is scarce.…”
Section: Discussionmentioning
confidence: 98%
“…Several strategies have been employed to enhance the bioactivity of zirconia ( Cengiz et al, 2016 ), such as sandblasting ( Moritz et al, 2019 ), acid etching ( Yu et al, 2021 ) and diverse bioactive coatings comprising silica, zinc and various compounds ( Ke et al, 2017 ). These approaches can create a biologically active surface on zirconia implants.…”
Section: Introductionmentioning
confidence: 99%
“…In most studies concerning zirconia etching with an HF solution, etching has occurred only for a relatively short time of 5 to 10 min 12,16) . This practice seems to be derived from the etching time associated with the use of lowconcentration HF for conventional ceramic materials.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been studies 16,17) exploring the effect of zirconia surface roughness and phase transformation on bond strength using various concentrations of HF and at diverse temperatures, few have specifically studied the changes in the physical properties of the zirconia surface depending on the application time of HF etching. This study aims to investigate the changes in the degree of phase transformation, surface roughness and bonding strength when the zirconia surface is immersed in the high concentration (40%) and room temperature of the HF solution for various times and find the optimal immersion time.…”
Section: Introductionmentioning
confidence: 99%